Uses and Gratification: Multiple Account Instagram Mahasiswa Universitas Udayana - Putri, Zahwadiva Sosiawan; Ranteallo, Ikma Citra; Nugroho, Wahyu Budi (JURNAL ILMIAH SOSIOLOGI: SOROT, 2025)
Instagram is one of the important social media platforms that has been researched before. Some Instagram users use more than one, to fulfill the need to consume diverse content and interact with other users. This research aims to research the needs that Instagram users want to meet, by using more than one account. These needs are also determined by the user's identity being displayed to the public and the private identity being hidden, as well as aiming to interact with social groups, seek pleasure and so on. This study uses a descriptive qualitative method to describe the needs of Instagram users who have more than one account, based on the uses and gratification theory of Katz, Blumer and Gurevitch. The results of this study show that the use of multiple Instagram accounts can help students adjust and become an effective strategy to meet various needs, including information, emotional, personal integration, social integration, and entertainment needs.